Phenotypic Correlation, Path Analysis, and Quantitative Trait-Based Selection of Elite Wheat Genotypes Under Heat Stress Conditions in The Terai Region of Nepal - Bhandari, Radhakrishna; Panthi, Binod; Nyaupane, Shivalal; Shrestha, Sandesh; Sharma, Prabin; Gupta, Rajesh Kumar; Sahani, Sansar; Poudel, Mukti Ram (Makara Journal of Science, 2024)
Wheat is one of the most important cereal crops worldwide, but the production and productivity of wheat is affected by heat stress. A field experiment using an alpha lattice design with seven blocks was conducted on 35 elite wheat genotypes in the Terai region of Nepal to identify the most appropriate trait resulting in a high-yielding wheat genotype with high tolerance to heat stress. Correlation analysis revealed that booting-to-heading duration (BtoH), booting-to-anthesis duration (BtoA), plant height (Ph), spike length (SL), spike weight (SW), thousand grain weight (TGW), straw yield (SY), and total biomass yield (TY) had a significant positive correlation with grain yield (GY), whereas days to booting (DTB), days to heading (DTH), and days to anthesis (DTA) had significant negative correlations with GY (p ≤ 0.05). Path analysis revealed that DTB and DTA had a direct negative effect on the GY, whereas DTH had an indirect negative effect on yield via DTB. BtoA, Ph, SL, SW, and TGW had direct positive effects on yield, whereas BtoH had an indirect positive effect on yield via DTB. Principal component analysis demonstrated that high-yielding genotypes can be selected using DTB, DTH, DTA, BtoH, BtoA, and Ph. Taller and earlier genotype with long BtoH and BtoA would produce high yield under heat stress.